Green Product, Social Media Marketing and Its Influence on Purchasing Decisions - Ni Luh Bayu Okadiani; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (International Journal of Applied Business and International Management, 2019)
This study aims to determine the effect of green product and social media marketing on purchasing decisions. Environmental problems become one of the considerations for consumers to start using a green product. While social media marketing is a means for companies to who participate in social media so that later it will produce purchasing decisions. This is a study on Sensatia Botanical products. In this study using a nonprobability sampling method with a number of 100 respondents. This study found that green products have a positive and significant effect on purchasing decisions with the regression value of the green product variable is 0.614. Whereas social media marketing does not have a significant effect on purchasing decisions.